The Influence of Work-Family Conflict, Workload, and Work Pressure as Mediating Variables on the Performance of Female Employees - Arnova Linda; Rino Rino (LPPM Universitas Terbuka, 2023)
Purpose – The main purpose of this study was to assess how Work-Family conflict, workload, and work stress function as mediating factors influencing the performance of female employees at BPS (Central Bureau of Statistics) in the West Sumatra Province. Methodology – This quantitative investigation was conducted using a survey approach, with the sample consisting of 188 married or formerly married female employees out of a total of 128 participants. A questionnaire was used as an instrument which was designed using Google form and consisted of 58 questions. Furthermore, the sampling was carried out using Cluster Sampling, with districts/cities serving as the clusters. Descriptive statistical and Partial Least Square (PLS) analyses were adopted for the data analysis process using the Smart PLS 3.2.3 program. Findings – The results showed that workload and Work-Family conflict had a positive influence on both work pressure and the performance of female employees. Meanwhile, Work-Family conflict and work pressure negatively influenced the performance of female employees. A negative influence was also observed on the performance of women employees due to Work-Family conflict, mediated through work pressure. Originality – This research investigated the influence of Work-Family conflict and workload on the performance of women employees, mediated by job pressure.